EFEKTIFITAS KOMBINASI PENGHANGAT AIR TERKENDALI PADA SISTEM RESIRKULASI AIR UNTUK PEMBENIHAN IKAN - Mochamad Bagus Hermanto; Budi lndra Setiawan; Rudiyanto Rudiyanto (PERTETA, 2007)
ABSTRACT Efficacies in hatchery depend on the ability to control water temperature. The aim of this research is to reduce heat loss in hatchery room, so that the energy requirement for water warming will be more efficient. Two units of flat plate solar collectors were serially installed. On-off controller is used to control a fan which is used for air re-circulation in 6m x 4m x 3m closed room. Experiments were carried out to find effectiveness of solar collector as a controlled warmer unit by perceived both temperature and relative humidity parameters. Initial experiment results indicate that solar collector as a warmer unit is able to give mean room temperature with tow standard deviation. The statistical analysis results also indicate that the mean water temperature at the controlled air re-circulation system with circulating water is equal to 27. 6 0C with standard deviation equal to 0.7 0C. Additional 350 Watt of electric water warmer can increase the mean water temperature that is equal to 30.6 0C with standard deviation equal to 0.5 0C which is an ideal environment for fish hatcher. It concludes that the combination of solar collector and electric water warmer as a controlled warmer unit is able to give mean water temperature with low standard deviation, so that this system can effectively reduce the use of warming energy cost until 76.85 %. Diterima: 1 Ncpemoer 2006: Disetujui: 20 Nopember 2006